Por uma teologia da imagem em movimento : uma troca de olhar com o cinema a partir da obra de Andrei A.Tarkovski, no horizonte da Teologia de Paul Tillich. - Santos, Joe Marçal Gonçalves dos (2006)
A study about the cinematographic look centered on the work of the Russian director ANDREI ARSENSEVICH TARKOVSKI (1934-1986), in the perspective of an esthetic-theological reception of film as reference for a theology of the image-in-movement. The first chapter is the development of an ontogenesis of film creation, through an analysis of the artisticbiographical career of Tarkovski, aiming at delineating the formation of a look out of the relation between author and work, which Tarkovski understood as the organic relation on which all art depends. The second chapter is an analysis of Tarkovski´s last film, The Sacrifice (Sweden, 1986). It starts with a synopsis of the film and then details the image moved by Tarkovski´s camera, understanding it as a economy of the look which the artist create in the film. A third moment in this chapter describes the look exchange with the film in a theopoetic synoptic as a perspective of a theological look on the film. The third chapter presents the moment of theological theory. The aim is to construct the cognitive relation between theology and cinema from the metaphor of a theological look . In a second moment it defines the object of a theology of the image in movement as the mediation of a look. In a third moment, the communicative situation of esthetic-theological reception of film is defined as a look exchange out of which the idea of a theopoetic synoptic as a theological critical-creative perspective of cinematographic interpretation is developed. The study is about the experience of esthetic reception of film, centering on its implications for the subject of the theological look. It affirms the heuristic value of cinema for theology as experience of a look crisis and, at the same time, the experience of a creative and self-transcendent look.